Voice conversion by speech synthesis - Lee, Ming Hui. (2009)
Speech signal contains two kinds of information. They are: (i) The message the speaker wants to convey to the listener and (ii) the characteristics of the speaker. In this project, we focus on the analysis and manipulation of speaker characteristics embedded in the speech signal for voice conversion. Voice conversion involves transformation of the speaker characteristics in the speech uttered by a speaker (source speaker), so as to generate speech having the voice characteristics of the desired speaker (target speaker).